STUDI KELAYAKAN RENCANA PENDIRIAN RUMAH PEMONDOKAN (KOST) KELAS MENENGAH DI TEGALGONDO MALANG - Rahmawati, Fifi (Department of Management, 2015)
The purpose of this research is to determine lodging house feasibility in Malang. Feasibility study includes marketing aspects, technical, economic and social, management, legal, environmental, and financial aspects. Analysis tools used are Net Present Value (NPV), Payback Period (PP), Method of Average Rate of Return (ARR), Method Internal Rate of Return (IRR), and Profitability Index (PI). The results show that ARR is 24% (more than 17% minimum requirement), PP is 6.2 year (less than 15 year proposed), NPV is 485.041 (more than 0), IRR is 17.013% (more than 17% ARR), and PI is 1.0007287 (more than > 1). All the feasiblity requirement are eligible. It means that the lodging house project is feasible.